Adaptation to acidic soil is achieved by increased numbers of cis‐acting elements regulating ALMT1 expression in Holcus lanatus. (25th July 2013) - Chen, Zhi Chang; Yokosho, Kengo; Kashino, Miho; Zhao, Fang‐Jie; Yamaji, Naoki; Ma, Jian Feng
Summary: Yorkshire fog ( Holcus lanatus ), which belongs to the Poaceae family and is a close relative of the agronomic crop oat ( Avena sativa ), is a widely adaptable grass species that is able to grow on highly acidic soils with high levels of Al, but the mechanism underlying the high Al tolerance is unknown. Here, we characterized two accessions of H. lanatus collected from an acid plot (soil pH 3.6, HL–A) and a neutral plot (pH 7.1, HL–N) in terms of Al tolerance, organic acid anion secretion and related gene expression. In response to Al (pH 4.5), the HL–A roots secreted approximately twice as much malate as the HL–N roots, but there was no difference in citrate secretion. Cloning of the gene HlALMT1 responsible for malate secretion showed that the encoded amino acid sequence did not differ between two accessions, but the expression level in the outer cell layers of the HL–A roots was twice as high as in the HL–N roots. This difference was not due to the genomic copy number, but was due to the number of cis ‐acting elements for an Al‐responsive transcription factor (HlART1) in the promoter region of HlALMT1, as demonstrated by both a yeast one‐hybrid assay and a transient assay in tobacco protoplasts. Furthermore, introduction of HlALMT1 driven by the HL–A promoter into rice resulted in significantly more Al‐induced malate secretion than introduction of HlALMT1 driven by the HL–N promoter. These findings indicate that the adaptation of H. lanatus to acidic soils may be achieved by increasing number of cis ‐acting elements for ART1 in the promoter region of the HlALMT1 gene, enhancing the expression of HlALMT1 and the secretion of malate.